Acquisition of developmental competence and in vitro growth culture of bovine oocytes - Masashi NAGANO (The Society for Reproduction and Development, 2019)
Recently, the demand of transferable embryos in cattle industry is increasing, and the number of embryos produced in vitro is also increasing in the world. Although oocytes are collected from individual elite cattle by ovum-pick up (OPU) and used for in vitro production (IVP) of embryos, the cattle are mono-ovulatory animal. It means that most of oocytes collected from ovaries are destined to degenerate. To improve the IVP efficiency, we should predict the developmental competence of oocytes correctly and culture them by the suitable way. In addition, in vitro production of bovine oocytes by in vitro growth (IVG) culture system will become a candidate of supply source of oocytes for IVP. If we can produce high competent oocytes by IVG, IVP efficiency will be improved and the genetic improvement of cattle will be dramatically accelerated. In the review, I introduce our researches related to oocyte morphology, the developmental competence, and the production of oocytes having high developmental competence by IVG culture.